MicroRNA profile changes in human immunodeficiency virus type 1 (HIV-1) seropositive individuals - Houzet, Laurent (BioMed Central, 2008)
MicroRNAs (miRNAs) play diverse roles in regulating cellular and developmental functions. We have profiled the miRNA expression in peripheral blood mononuclear cells from 36 HIV-1 seropositive individuals and 12 normal controls. The HIV-1-positive individuals were categorized operationally into four classes based on their CD4+ T-cell counts and their viral loads. We report that specific miRNA signatures can be observed for each of the four classes.